LEGAL INFORMATION APPLICATION MODEL AT THE SINGKAWANG CITY REGIONAL SECRETARIAT OFFICE - Darmawan, Deni (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2023)
This research aims to analyze the standardization of the JDIHN website from perspective legal application model developed and managed by the City Regional Secretariat Singkawang. The method used is descriptive research with qualitative approach, especially regarding the application of website-based legal information at JDIH Singkawang City, studied based on the pressman's star life cycle theory Rusdiana and Irfan (2014). Data collection techniques use techniques for interviews, observation and documentation. Data were analyzed using data analysis techniques domain, as a researcher's effort to get a general picture and comprehensive (holistic) of the object under study. The results of the research are 1) design administrative concepts related to public needs for documents and information complete, accurate, easy and fast laws have not yet been fulfilled sustainable; 2) the technical requirements for website-based processing are in place meet minimum standards; 3) analysis of function assignments according to metadata standards; 4) The management's operational implementation has not been sustainable since 2020 however the website remains active and can be accessed by the public; 5) website performance is not optimal GTMetrix indicator measurements. Keywords: JDIH, Legal Information, Website